1992
DOI: 10.1021/ac00030a021
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic organic analysis using two-step laser mass spectrometry: application to meteoritic acid residues

Abstract: We have developed a mlcroanalytlcal Instrument to analyze the organk constltuonts of partlculates and Inhomogeneous samples wtth aspaUal ramlutbn ol approxlmatdy 40 pm. Om method, two-step laser desorptlon/laser lonlzatlon mass spectrometry (L2MS), uses an Infrared laser to volatlllze constttuent mokuks Intact and an ultraviolet l a w to lonlze desorbed molecules In a selective manner with Imle or no frcrqrwntcrtion. In partlcular, our lnrtrwnent Is currently tuned to detect polycycllc aromatic hydrocarbons (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 33 publications
0
57
0
Order By: Relevance
“…The development of this device has also benefited greatly from the contributions of several postdoctoral research associates including F. Engelke, J.-M. Phillipoz, L. J. Kovalenko, and X. D. F. Chillier. The detailed applications of this instrument to the study of meteoritic samples may be found elsewhere Zenobi et al 1989Zenobi et al , 1992Kovalenko et al 1991Kovalenko et al , 1992Zenobi h Zare, 1991;Clemett et al 1993;Thomas et al 1995a;Maechling et al 1995;McKay et al 1996). In what follows we emphasize the capabilities of this analytic tool and its present limitations.…”
mentioning
confidence: 91%
“…The development of this device has also benefited greatly from the contributions of several postdoctoral research associates including F. Engelke, J.-M. Phillipoz, L. J. Kovalenko, and X. D. F. Chillier. The detailed applications of this instrument to the study of meteoritic samples may be found elsewhere Zenobi et al 1989Zenobi et al , 1992Kovalenko et al 1991Kovalenko et al , 1992Zenobi h Zare, 1991;Clemett et al 1993;Thomas et al 1995a;Maechling et al 1995;McKay et al 1996). In what follows we emphasize the capabilities of this analytic tool and its present limitations.…”
mentioning
confidence: 91%
“…In one research project, two such particles exhibited broad PAH envelopes (29), as well as other signatures (28,30,31), which confirmed their identification as IDPs. PAHs were found to cluster in three mass envelopes (with peaks at 60, 250, and 370 amu) and exhibited more extensive alkylation and nitrogen addition (i.e., -NH 2 , -CN, or -NC) than those observed in carbonaceous chondrites (14,19,20). Relative to carbonaceous chondrites, a strikingly low abundance of PAHs Ͻ192 amu was found.…”
Section: Interplanetary Dust Particles (Idps)mentioning
confidence: 93%
“…The degree of PAH alkylation [PAH-(CH 2 ) n ], in particular, was characterized in carbonaceous chondrites (15,19,20) and Antarctic micrometeorites (AMMs) (21), which represent a range of thermal and aqueous alteration histories. Increasing PAH alkylation was found to associate with increasing aqueous exposure of carbonaceous chondrite parent bodies (19).…”
Section: Review Of L 2 Ms For the Study Of Extraterrestrial Materialsmentioning
confidence: 99%
“…Of course, PAHs have also been analyzed in carbonaceous chondrites (Pering and Ponnamperuma, 1971;Clemett et al, 1992;Kovalenko et al, 1992). However, the rapid contamination of newly fallen meteorite material (e.g., the Allende fall in 1968) by terrestrial organic compounds (Han et al, 1969) suggests caution in interpreting results, and requires rigorous background control and blank analyses.…”
Section: Nonbiomarkersmentioning
confidence: 99%